PENGARUH KOMPOSISI KARBON AKTIF, ZEOLIT, DAN PASIR SILIKA DALAM MENURUNKAN WARNA AIR SUMUR GALI DI DESA SUNGAI SEGAJAH JAYA - Abdul Halim Daulay; Masthura Masthura; Jefri Ardiansyah Nasution (JISTech (Journal of Islamic Science and Technology), 2021)
Research has been carried out to find out how the quality of dug well water before and after being filtered using activated carbon, zeolite, and silica sand, and to find out how the composition of the mixing of activated carbon, zeolite, and sand is to produce clean water with the most optimum quality for color parameters. based on PERMENKES RI No. 32 of 2017. This study uses dug well water from Sungai Segajah Jaya Village, Kubu District, Rokan Hilir Regency, Riau Province. The composition of activated carbon, zeolite, and silica sand used is 60%:20%:20%, 50%:25%:25%, and 40%:30%:30%. The test results of dug well water samples before applying the filtering method for color. The test results of dug well water samples after applying the filtering method with activated carbon, zeolite, and sand with a composition of 60%:20%:20%, 50%:25%:25%, and 40%:30%:30 %, for the color parameter has met the standard of clean water quality based on PERMENKES RI No. 32 of 2017. From the three variations in the composition of the filter material, the optimum composition of mixing activated carbon, zeolite, and silica sand in the filter was obtained with a composition of 40%:30%:30%. This is shown from the test results data, the results of sample D for color parameters are better according to the maximum limit standard allowed by PERMENKES RI No. 32 of 2017 concerning the requirements for clean water quality, namely 32 TCU.